Is this America? Unfinished business with the U.S. national imaginary, religion and violence. Issue 1 (4th March 2019) - Denton‐Borhaug, Kelly
Abstract: This article first proposes definitions and raises questions about what it means to be a nation. I then analyze the national imaginary of the United States, and suggest that at its deepest core we find "substitute ultimates" regarding America's sacrificial war‐culture. This cultural violence perpetuates destructive consequences, including the phenomena of "U.S. war‐culture, " and "moral injury" among military servicemembers and veterans. But widespread legitimation of the imaginary largely inhibits citizens from awareness about their own reality. Lastly, I inquire about the role of prophetic public theology to address nationalism, and engage in a thought experiment with an imagined community of diverse partners.